Analisis Pemanfaatan Artificial Intelligence (AI) sebagai Referensi dalam Desain Komunikasi Visual - Muhammad Muhaemin (Jurnal SASAK : Desain Visual dan Komunikasi, 2023)
This research aims to explore and analyze the utilization of Artificial Intelligence (AI) as a reference in creating works in Visual Communication Design. The research method used is exploratory research, which aims to explore a specific topic or issue in more depth and gain a better understanding of it. The research procedure conducted includes: 1) Understanding keywords, 2) Testing the use of prompts on AI sites, and 3) Analyzing the data descriptively and analytically. The result obtained is that Artificial Intelligence (AI) image sites can be used as a reference in creating works of Visual Communication Design by deepening and clarifying the use of prompt sentences. The implication of this research is to consider the utilization of Artificial Intelligence (AI) image sites as a reference for creating works.